Integration of scientific knowledge into Islamic juridical work the search for a unified legislative framework - Haneef, Sayed Sikandar Shah (Kulliyyah of Science, IIUM, 2011)
Technological advancement in the field of medicine and its allied sciences continues to unfold new questions for juridical response from the contemporary jurists. In consequence, in the recent past a great deal of juridical opinions (fatawa),at the behest of both individual jurists and official bodies, have piled up. However, a reflective survey of the existing literature reveals that when it comes to reconciling the scientific findings with the purport of textual imperatives, the jurists by and large go bipolar, namely, either accept them all in sundry or reject them in totality. This state of affairs, among other medico-ethical implications, tends to have far-reaching implications for Muslim families particularly if they want to make a choice between such contrasting positions. To put things in true perspective, this study proposes to take the law of abortion as a case study with the purpose of identifiying appropriate Islamic juridical frameworks by which the juristic divide on the issue in question could be synchronized.